2000
DOI: 10.1080/02757250009532406
|View full text |Cite
|
Sign up to set email alerts
|

The IWMMM‐2 conference: Background, achievements and recommendations

Abstract: Japan. These participants, listed in Annex 1, were involved or interested in modeling the anisotropy of the radiation field, in multiangular measurements, or in the exploitation of these tools and data in their own applications.This 3-day meeting addressed three main objectives: (1) to establish the state of the art in direct and inverse modeling techniques, including those proposed for the operational exploitation of earlier instruments * Corresponding author. 1 Downloaded by [University of Tennessee, Knoxvil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…As already concluded by Verstraete and Pinty (2001), researchers in the field of multi-angular remote sensing are constantly facing the problem of "bridging the gap between theoretical studies of anisotropy and practical applications to exploit these features". With some of the presented studies it is shown that significant process has been made over the last years and a great variety of possible applications for multiangular remote sensing is apparent.…”
Section: Discussionmentioning
confidence: 99%
“…As already concluded by Verstraete and Pinty (2001), researchers in the field of multi-angular remote sensing are constantly facing the problem of "bridging the gap between theoretical studies of anisotropy and practical applications to exploit these features". With some of the presented studies it is shown that significant process has been made over the last years and a great variety of possible applications for multiangular remote sensing is apparent.…”
Section: Discussionmentioning
confidence: 99%